Development of Website-Based KOMIK ALAM (E-comic Utilization of Natural Resources) as Social Studies Learning Media - Qonita Rahma Zahira; Neni Wahyuningtyas; Ravinesh Rohit Prasad (International Journal of Social Learning (IJSL), 2025)
The use of e-comics in social studies learning is gaining popularity due to their ability to convey concepts visually. However, students still face difficulties in understanding the material, as e-comic storylines are often not contextual and do not present real-world problems. This study aims to develop KOMIK ALAM, a website-based e-comic learning media focused on natural resource utilization for Grade VIII students at MTs Negeri 2 Malang City. The research employs an R&D method utilizing the Design Thinking development model, which encompasses four stages: empathize, define, ideate, and prototype. The study focused on prototype development without proceeding to the test stage. Validation from subject and media experts, as well as a readability test with students, indicated that KOMIK ALAM is highly feasible. KOMIK ALAM is expected to serve as a visual and interactive learning media that presents contextual content and real problems to support diverse learning styles and increase student engagement. Future research should examine its effectiveness through experimental methods.